2012
DOI: 10.1111/j.1478-3231.2012.02837.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral CCN3/NOV gene transfer fails to mitigate liver fibrosis in an experimental bile duct ligation model because of hepatocyte apoptosis

Abstract: Even though Ad-NOV gene transfer in a 3-week bile duct ligation mouse model showed the expected high levels of CCN3/NOV in both mRNA and protein, it failed to reduce liver fibrogenesis, but instead enhanced hepatocyte apoptosis. Furthermore, overexpressed CCN3/NOV in cultured primary hepatocytes resulted in decreased levels of CCN2/CTGF, the profibrotic marker protein in liver fibrosis. Both Ad-NOV and Ad-CTGF induced reactive oxygen species production, enhanced p38 and JNK activation. Therefore, we conclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…This hypothesis was reinforced by the fact that overexpression of NOV in vascular smooth muscle cells inhibited the angiotensin II profibrotic effects by down regulating both AT 1 R and CTGF expressions (Marchal PO et al, 2014 submitted manuscript). These observations are in line with previous data showing that the suppression of NOV enhanced expression of profibrotic marker proteins, such as α-smooth muscle actin, collagen type I, and CTGF in primary rat hepatic stellate cells [ 32 ]. In addition, overexpression of NOV reduced glomerulosclerosis and cortical accumulation of collagen type I in progressive glomerulonephritis [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This hypothesis was reinforced by the fact that overexpression of NOV in vascular smooth muscle cells inhibited the angiotensin II profibrotic effects by down regulating both AT 1 R and CTGF expressions (Marchal PO et al, 2014 submitted manuscript). These observations are in line with previous data showing that the suppression of NOV enhanced expression of profibrotic marker proteins, such as α-smooth muscle actin, collagen type I, and CTGF in primary rat hepatic stellate cells [ 32 ]. In addition, overexpression of NOV reduced glomerulosclerosis and cortical accumulation of collagen type I in progressive glomerulonephritis [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the nature of the interactions in distinct physiopathological contexts can also govern the ability of NOV to interact with various partners providing contradictory results. Of note, recent studies showed that adenoviral NOV gene transfer failed to attenuate fibrogenesis in an in vivo model of experimental liver fibrosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) levels were measured as previously described 21. In brief, mouse hepatocytes were cultured on collagen‐coated glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…In our laboratory, we have extensively used this protocol in the past in rats in several experimental studies aiming to investigate special molecular and cellular aspects of hepatic fibrogenesis and to test novel antifibrotic concepts and drugs [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%